Effects of select medium supplements on in vitro development of Cryptosporidium parvum in HCT-8 cells. - Upton, S J (1995)
Surface-sterilized oocysts of Cryptosporidium parvum were applied to subconfluent monolayers of human adenocarcinoma (HCT-8) cells grown on coverslips in six-well cluster plates. Parasite-infected cultures were then incubated in RPMI 1640 with 10% fetal bovine serum, 15 mM HEPES (N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid) buffer, and antibiotics at 37 degrees C in a 5% CO2-95% air incubator for 2 h to allow sporozoites to excyst and enter cells. After cultures were washed free of debris, fresh cell culture media containing select supplements were added and cultures were reincubated. Parasite growth was assessed 66 h later by counting the number of parasite developmental stages in 25 random x 100 oil fields by Nomarski interference-contrast microscopy. Four vitamin supplements, calcium pantothenate, L-ascorbic acid, folic acid, and 4-(para)-aminobenzoic acid, each resulted in a significant increase in parasite numbers in vitro. The addition of insulin and the sugars glucose, galactose, and maltose also had a positive effect on parasite growth, although the effect was less pronounced than with any of the vitamins. Using the above information, we developed a supplemental medium formulation consisting of RPMI 1640 with 10% fetal bovine serum, 15 mM HEPES, 50 mM glucose, and 35 micrograms of ascorbic acid, 1.0 micrograms of folic acid, 4.0 micrograms of 4-aminobenzoic acid, 2.0 micrograms of calcium pantothenate, 0.1 U of insulin, 100 U of penicillin G, 100 micrograms of streptomycin, and 0.25 microgram of amphotericin B (Fungizone) per ml (pH 7.4).(ABSTRACT TRUNCATED AT 250 WORDS)